Semi-commutativity criteria and self-coincidence elements expressed by vectors properties of n-ary groups - Kulazhenko, Yu.I. (Algebra and Discrete Mathematics, 2010)
In this paper new criteria of semi-commutativity and results on self-coincidence of an arbitrary point P in the terms of properties of vectors of n-ary groups are obtained.